Pemanfaatan Media Pembelajaran Smartphone Aplikasi Bertimah Dalam Kegiatan Belajar Mengajar PAI di SD Negeri 22 Mentok - Isriyanto (4, 2026)
In the context of education, technology integration presents new opportunities to improve the quality of the learning process, one of which is through the use of smartphones as a learning medium. This study specifically focuses on the use of Android-based smartphones through the Bertimah application as a learning medium for Islamic Religious Education (PAI) at SD Negeri 22 Mentok. The focus of the research is directed at identifying the stages of utilization, advantages, and challenges of using the Bertimah application in PAI learning. This study is motivated by the need to describe in depth how smartphone-based learning media can be effectively integrated into PAI learning at the elementary school level. This study uses a qualitative approach with a descriptive research type, which aims to obtain a comprehensive picture of the process and various aspects related to the use of the Bertimah application in PAI learning. Data collection techniques are carried out through observation, interviews, and documentation. The data obtained are analyzed through three main stages, namely data reduction, data presentation, and drawing conclusions or verification, to ensure in-depth, thorough, and accurate research results in accordance with field conditions. The results of the study show three main findings. First, the use of the Bertimah application smartphone learning media is implemented through two learning contexts, namely in the classroom and at home. Second, the use of the Bertimah app offers various benefits for both schools and students, such as improved school performance and student learning outcomes. Third, this study also identified several challenges, including limited devices and internet access, potential disruption and misuse of smartphones, Islamic Religious Education (PAI) teacher preparedness, and the need for ongoing application development and maintenance. Overall, this study provides a comprehensive overview of the implementation, benefits, and obstacles to integrating smartphone technology into Islamic Religious Education (PAI) learning in the digital era. Abstrak Dalam konteks pendidikan, integrasi teknologi menghadirkan peluang baru dalam meningkatkan kualitas proses pembelajaran, salah satunya melalui pemanfaatan smartphone sebagai media belajar. Penelitian ini secara khusus berfokus pada penggunaan perangkat smartphone berbasis Android melalui aplikasi Bertimah sebagai media pembelajaran Pendidikan Agama Islam (PAI) di SD Negeri 22 Mentok. Fokus penelitian diarahkan untuk mengidentifikasi tahapan pemanfaatan, keuntungan, serta tantangan penggunaan aplikasi Bertimah dalam pembelajaran PAI. Kajian ini dilatarbelakangi oleh kebutuhan untuk mendeskripsikan secara mendalam bagaimana media pembelajaran berbasis smartphone dapat diintegrasikan secara efektif dalam pembelajaran PAI di tingkat sekolah dasar. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif, yang bertujuan untuk memperoleh gambaran yang komprehensif mengenai proses dan berbagai aspek yang berkaitan dengan pemanfaatan aplikasi Bertimah dalam pembelajaran PAI. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Data yang diperoleh dianalisis melalui tiga tahapan utama, yaitu reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi, guna memastikan hasil penelitian yang mendalam, teliti, dan akurat sesuai dengan kondisi lapangan. Hasil penelitian menunjukkan tiga temuan utama. Pertama, pemanfaatan media pembelajaran smartphone aplikasi Bertimah diimplementasikan melalui dua konteks pembelajaran, yaitu di kelas dan di rumah. Kedua, penggunaan aplikasi Bertimah memberikan berbagai keuntungan, baik bagi sekolah maupun siswa, seperti peningkatan prestasi sekolah dan hasil belajar siswa. Ketiga, penelitian ini juga menemukan sejumlah tantangan, antara lain keterbatasan perangkat dan akses internet, potensi gangguan dan penyalahgunaan smartphone, kesiapan guru PAI, serta kebutuhan pengembangan dan pemeliharaan aplikasi secara berkelanjutan. Secara keseluruhan, penelitian ini memberikan gambaran utuh mengenai implementasi, manfaat, dan hambatan integrasi teknologi smartphone dalam pembelajaran PAI di era digital.